Status and epidemiological characteristics of high-risk human papillomavirus infection in multiple centers in Shenyang - Yang, Di; Zhang, Jing; Cui, Xiaoli; Ma, Jian; Wang, Chunyan; Piao, Haozhe (Frontiers in Microbiology, 2022)
The different human papillomavirus (HPV) strains cause warts in various regions of the body. However, considering that the status and genotype distribution of HPV infection in women in Shenyang remain unknown, herein, we investigated the epidemiological characteristics of high-risk HPV (HR-HPV) infection in women in Shenyang, as well as the current state of HPV infection in Shenyang, to provide a theoretical basis for the prevention and treatment of cervical cancer. From December 2018 to December 2021, 6,432 urban and rural women from the Liaoning Cancer Hospital and the Sujiatun Women and Infants’ Hospital were assessed via the Thinprep cytology test (TCT) and HR-HPV detection. Of the 5,961 women enrolled, 739 were HPV positive (12.40%) and 562 were TCT positive (9.43%). Statistical analyses identified the following HPV risk factors: high school education or lower [OR = 1.426 (1.199–1.696), p < 0.001], age at first sexual encounter ≤ 19 years [OR = 1.496 (1.008–2.220), p = 0.046], and number of sexual partners > 1 [OR = 1.382 (1.081–1.768), p = 0.010], atypical squamous cells of undetermined significance (ASCUS) and above [OR = 10.788 (8.912–13.060), p < 0.001], non-condom-based contraception [OR = 1.437 (1.103–1.871), p = 0.007], nationalities other than Han [OR = 1.690 (1.187–2.406), p = 0.004], rural residence [OR = 1.210 (1.031–1.419), p = 0.020]. Compared to the HPV infection rate of women aged 56–65, that in women aged 35–45 [OR = 0.687 (0.549–0.860), p = 0.001] and 46–55 [OR = 0.740 (0.622–0.879), p = 0.001] decreased significantly. To conclude, risk factors of HPV infection among female patients include high school age and below, initial sexual encounter at age ≤ 19 years, number of sexual partners > 1, ASCUS and above, non-condom contraception, nationalities other than Han nationality and rural population. Collectively, this study provides insights for the improved prevention and treatment of cervical cancer.